(untitled) (Baghdad Science Journal, 2013)
A program in Visual Basic language was designed to predict the type of radio storm that emitted from Jupiter at specific Local Time (LT) from two different Iraqi locations (Baghdad and Basra), such storms result from the Central Meridian Longitude (CML) of system ??? for Jupiter and phase of Io’s satellite (?Io). Some of these storms are related to position of Io (Io- A,B,C,D) and others are unrelated (non-Io-A,B,C,D) to its position. The input parameters for this program were user specified by determining the observer’s location (longitude), year, month and day. The output program results in form of tables provides the observer with information about the date and the LT of beginning and end of each type of emitted storm. Two Io-storm ranges were used in this program according to the standard observations, one of them at year 2008 and the other one at 1976, the results according to year 2008 gave the observer more types of storms as compared with results that depending on 1976, these results indicated the type of storm is not changed for these two locations, but their LT was changed, because it depend on the location of the observer. The obtained results reveal a good agreement as compared with the results of (Radio Jove) software.